A preliminary phylogeny of the South African Lentulidae. (December 2016) - Matenaar, Daniela; Bröder, Linda; Hochkirch, Axel
Abstract Background The grasshopper family Lentulidae is endemic to eastern and southern Africa, with its center of diversity situated in South Africa, the highest diversity being found in the Cape Floristic Region, which is one of the global biodiversity hotspots. The family consists of 35 genera sorted in two subfamilies. This study provides first insights into the phylogeny of Lentulidae. Two mitochondrial genes (12S and NDS) were sequenced and the phylogeny was inferred through Maximum Likelihood and Bayesian Inference. Results Our results indicate that the current classification into the subfamilies Lentulinae and Shelforditinae may be incorrect asUvarovidium, Leatettix (Shelforditinae) andDevylderia (Lentulinae) clustered together in one main clade, whileBetiscoides, Basutacris andGymnidium (all Lentulinae) formed the second main clade. The generaUvarovidium andLeatettix, which had been assigned to the Acrididae (subfamily Hemiacridinae) in the past, grouped within the Lentulidae, confirming their current assignment to this family. The East AfricanUsambilla group is likely to represent a sister clade to the south AfricanLentula andEremidium . Diversification patterns in the genusDevylderia andBetiscoides suggest a higher number of species than currently known. Conclusions Our phylogeny is not in line with the current systematics of Lentulidae, suggesting that a broader sampling and a study of the genitalia would be useful to clarify the taxonomy. Furthermore, some genera (particularlyBetiscoides andDevylderia ) are in need of taxonomic revision, as the number of species within these genera is likely to be higher than the current taxonomy suggests.